Modeling and analysis of change management in dynamic business process - Rajabi, B.A.; Lee, S.P. (2010)
Many business processes are highly dynamic and require changes even during execution. Existing commercial Business Process Management Systems (BPMS) fail to support such processes appropriately since they work in a rather static manner; they demand that the structure of a process is fixed before execution. The aim of this research is to provide a change management technique to improve the flexibility, adaptability, and dynamic of the current Business Process Modeling (BPM) approaches, and to help software engineers by finding a systematic and methodical approach for change analysis and management.